Neoliberal Economic Policies’ Effects on Perceptions of Social Justice and Sociopolitical Participation in Portugal - Lucas Casanova, Mariana; Costa, Patrício; Lawthom, Rebecca; Coimbra, Joaquim L. (Frontiers in Psychology, 2021)
Contemporary societies challenge long-standing projects of the “good society” and social equality through neoliberal economic policies. Social forms of uncertainty generated by financial deprivation, precarity and inequality seem to have effects on agency and coping and so, socioeconomic and psychological consequences. This study aims to test these relationships, as well as a hypothesis on the potential impact of these constructs on beliefs of sociopolitical control and social dominance, which have implications for social justice. A mediation model explores the effects of financial access (the manifest benefit of work) on psychosocial uncertainty (which reflects the perception of uncertainty in the social context and the experience of its consequences within work, relationships, and the adoption of self-defeating beliefs), and on emotional coping strategies towards uncertainty, and their effects on personal agency, sociopolitical control (SPC) and social dominance orientation (SDO). Data is derived from a study of 633 participants in Portugal. Though personal agency is influenced by financial access and psychosocial uncertainty, it is not proved as a significant mediator for SPC and SDO. Nevertheless, financial access, psychosocial uncertainty and emotional coping significantly contribute to the model, supporting the hypothesis that financial access protects against psychosocial uncertainty. Both have an impact on SPC and SDO. Therefore, financial deprivation and psychosocial uncertainty potentially contribute to extremism and populism in societies characterized by socially created forms of uncertainty. Implications of results for psychological intervention, namely in vocational/professional counselling are discussed.